Enhanced Performance of Perovskite Solar Cells via Reactive Post‐treatment Process Utilizing Guanidine Acetate as Interface Modifier. Issue 11 (16th September 2021) - Patil, Pramila; Mann, Dilpreet Singh; Rondiya, Sachin R.; Dzade, Nelson Y.; Kwon, Sung-Nam; Na, Seok-In
Abstract : Organic–inorganic lead halide perovskites (OIHPs) have emerged as promising materials for next‐generation photovoltaics. However, performance improvements in the perovskite‐based device are still limited due to defects that exist more intensively on the surface as well as grain boundaries (GBs) and mismatching energy levels at the interface. Herein, a reactive post‐treatment process (RPP) using guanidine acetate (GA) is adopted to address defects and interfacial energy level matching at the perovskite surface. The RPP with GA (GA‐RPP) results in the formation of an improved perovskite layer with large grain size and low GB density, leading to the formation of secondary phases on the perovskite surface with appropriate energy levels, resulting in reduced defect density and charge recombination. Furthermore, density functional theory analysis reveals that the Pb‐rich secondary phase could improve the conduction of electrons at the perovskite interface. Therefore, the GA‐RPP‐based perovskite‐based solar cell (PSC) shows enhanced performance with 20.4% efficiency and long‐term stability. Abstract : Herein, a novel approach, a reactive post‐treatment technique using guanidine acetate, to enhance the grain size and introduce a secondary phase simultaneously is applied in a perovskite interface. The enhanced grain size helps to reduce the defect densities at the grain boundaries, while the secondary phases make the perovskite surface more n‐type, enhancing the device efficiency and stability.